Factors of Augmented Reality Technology Adoption in Influencing Attitude and Purchasing Intention: A Review on Advertising Context - et al., Fatrisha Mohamed Yussof (International Journal of Advanced Science and Technology, 2019)
The impact of globalization and technological advancement inevitably transformed communication and community interactions in social norms. It comes as no surprise when the global advertising industry has effortlessly switched from traditional media to digital media in audience engagement. In line with marketing 4.0 in the era of the fourth revolution, a new approach of integrating the world of realities and virtual worlds like augmented reality (AR) is being incorporated into marketing strategies. In the previous study uncovered that the adoption of technology can stimulate consumer’s interest in the product, which would then lead to the increased chances of purchase. In that light, this study seeks to address factors that influenced ads attitude and behavioral intention in the preceding empirical study. The technique used was a scope analysis approach which collects as many relevant data as possible including methods, variables or any significant inclusion to provide an overview of what was accomplished. A total of ten published papers were examined via scoping review. The results showed that inconsistency factor or variables and lack of understanding affect buying intention's consumer behavior. Moreover, most previous studies use magic mirror as stimuli that are imbalanced with three other AR paradigms. This concluded that augmented reality it is still at infancy that warrant further research to contribute to the enrichment of augmented technology adoption and knowledge in context of advertising.